2022
DOI: 10.3390/jcm11236970
|View full text |Cite
|
Sign up to set email alerts
|

Is There an Added Neonatal Risk in Vacuum-Assisted Deliveries with Nuchal Cord?

Abstract: This retrospective cohort study assessed the association between nuchal cord and adverse outcomes during vacuum-assisted delivery (VAD). Women with singleton pregnancies, 34–41-weeks gestation, who underwent VAD, from 2014 to 2020 were included. The primary outcome was umbilical cord pH ≤ 7.1. Secondary outcomes were neonatal intensive care unit admission, Apgar scores, pH < 7.15, subgaleal hematoma, shoulder dystocia and third/fourth-degree perineal tear. Outcomes were compared between neonates with (1059/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…This can result in oxygen supply disturbances. The risk factors considered to increase the frequency of umbilical cord wrapping are a long umbilical cord, male fetuses, hypertensive disorder, gestational diabetes, advanced maternal age, high maternal BMI, and multiparity [4][5][6][7]. According to some authors, it does not increase neonatal morbidity [8,9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can result in oxygen supply disturbances. The risk factors considered to increase the frequency of umbilical cord wrapping are a long umbilical cord, male fetuses, hypertensive disorder, gestational diabetes, advanced maternal age, high maternal BMI, and multiparity [4][5][6][7]. According to some authors, it does not increase neonatal morbidity [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…According to some authors, it does not increase neonatal morbidity [8,9]. Nevertheless, some of the conducted studies showed that cord entanglement may be associated with higher caesarean delivery rate [2,7,10], meconium-stained amniotic fluid [6,7], umbilical cord blood acidosis [1], reduced Apgar score [2,6,11], lower birth weight [5][6][7], or even stillbirth [12].…”
Section: Discussionmentioning
confidence: 99%